Non-vertical cave and dilution modelling at New Gold’s New Afton Mine - Parsons, J; Hamilton, D; Ludwicki, C (Caving 2018: Proceedings of the Fourth International Symposium on Block and Sublevel Caving, 2018)
New Gold’s New Afton Mine currently operates two separate caves: the West Cave and the East Cave. Both caves have seen external dilution and other symptoms of non-vertical cave growth towards the south. This non-vertical cave growth is believed to be caused by the weak picrite rock mass in the hanging wall. A geochemical analysis of the picrite unit identified marker elements that provided insight into the concept of non-vertical cave growth to the south; dilution pathways were identified, and the increase in picrite at certain locations across the footprint was incorporated into modelling the cave development. Advanced modelling techniques using Dassault Systèmes’ PCBCTM were employed to better model the complex flow behaviour. In the West Cave, the modelled draw cones were tilted to match the surface expression of the observed subsidence. In the East Cave, phantom drawpoints and forced cave backs were used to create a dilution model reflecting the picrite geochemical data. Both non-vertical PCBC cave models show improved reconciliations compared to the standard vertical mixing models. This paper outlines the methodology used in modelling the complex flow behaviour experienced at New Afton Mine, and the improved grade reconciliation between the standard vertical mixing model and a non-vertical mixing model.
Keywords: New Afton